PENINGKATAN HASIL BELAJAR BIOLOGI MELALUI PENERAPAN MODEL PEMBELAJARAN LANGSUNG (DIRECT INSTRUCTION) SISWA KELAS V SDN 029 RUMBAI PEKANBARU - Yustimar (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The background of this study is the low result of study biology class V students of SD Negeri 029 Rumbai, it is marked by the acquisition value of an average of 52.50. The low yield of this study because students are paying less attention to the teacher learning, passive learning of students in participating. This study is a class action that aims to improve learning outcomes biology, as well as improving the learning activities of teachers and students using direct learning model. Research was conducted during two cycles, where research on SDN 029 Rumbai with esearch subjects are students are students of class V with a total of 25 students. Data collection techniques used in this study was the observation techniques, test engineering and technical documentation. The analysis technique used is descriptive analysis. Based on the results of research and discussion, found that the learning outcomes of students has increased in each cycle is reinforced by the results that have been raised previously, namely: (1) in the first cycle biology mastery learning outcomes of students increased by 68%; (2) in the second cycle biology mastery learning outcomes of students increased by 88%; (3) in the first cycle of learning activities of students gained 84.42%, whereas in the second cycle of 83.62%; (5) in the first cycle of learning activities for teachers to get 82.96%, while the second cycle of activity the teacher's activities gained 84.09%. This indicates that the completeness kasikal has been reached, in which the research is successful if the completeness achieved 80% of students obtaining a minimum value of 65. Based on the results and the discussion can be concluded that the application of the model pembelajarn directly to improve learning outcomes biology class V students of SD Negeri 029 Rumbai, Pekanbaru.